Dopamine 2 Receptor Genes Are Associated with Raised Blood Glucose in Schizophrenia - Lawford, B.; Barnes, M.; Morris, P.; Noble, E.; Nyst, P.; Heslop, Karen; Young, R.; Voisey, J.; Connor, J. (Canadian Psychiatric Association, 2016)
Objective: Type 2 diabetes is commonly found in schizophrenia and is an important contributor to mortality and morbidity in this condition. Dopamine has been implicated in the aetiology of both diabetes and schizophrenia. It is possible that both disorders share a common genetic susceptibility. Methods: In a cross-sectional study, we examined 2 dopamine D2 receptor (DRD2) single-nucleotide polymorphisms (SNPs) previously associated with schizophrenia (C939 T, rs6275 and C957 T, rs6277) along with fasting blood glucose and body mass index (BMI) in 207 antipsychotic-treated patients with schizophrenia. All participants met DSM-IV criteria for schizophrenia, and those with other psychiatric disorders were excluded. Analysis of covariance was used to compare fasting glucose results by DRD2 genotypes, after controlling for known confounds. For significant associations, follow-up Bonferroni post hoc tests examined differences in fasting glucose levels between genotypes. Specific comparisons were also made using analysis of variance and chi-square (Fisher’s exact test). Results: The 2 DRD2 risk genotypes were associated with significant increases in blood glucose, after controlling for BMI, age, sex, dosage and type of antipsychotic medication, number of hospitalisations, and negative symptoms (rs6275, F(2, 182) = 5.901, P = 0.003; rs6277 SNP, F(2, 178) = 3.483, P = 0.033). Conclusions: These findings support the involvement of DRD2 not only in schizophrenia but also in elevated levels of blood glucose commonly found in antipsychotic-treated patients with schizophrenia. Our data support the notion that diabetes may not merely be a comorbid condition but could be fundamentally associated with the pathogenesis of schizophrenia itself.